O2–O3 chemodiscolysis: How much, how long? Retrospective outcome evaluation of different treatment sessions in partially-responder patients. Issue 4 (August 2022) - Bruno, Federico; Carboni, Nicola; Palumbo, Pierpaolo; Arrigoni, Francesco; Varrassi, Marco; Izzo, Antonio; Catallo, Nadia; Di Cesare, Ernesto; Masciocchi, Carlo; Splendiani, Alessandra; Giovagnoni, Andrea; Barile, Antonio
Purpose: To retrospectively evaluate the clinical and instrumental outcome of different treatment sessions of oxygen–ozone (O2 –O3 ) chemodiscolysis in patients with lumbar disc herniation Methods: We evaluated 73 patients partially responders to a single session of oxygen–ozone (O2 –O3 ) chemodiscolysis and submitted to multiple injections sessions. All patients completed a pre- and post-treatment clinical (VAS and modified McNab score) and instrumental MRI follow-up. Imaging evaluation included assessment of intervertebral disc area (IDA). Pre- and post-treatment differences were compared to evaluate differences in variation between groups. Correlation analysis was used to evaluate the relationship between morphological and clinical parameters. Results: Based on the type and number of treatments performed, patients were divided into three groups: Group A) patients submitted to an additional periradicular anaesthetic/steroid injection; Group B) patients submitted to an additional session of intradiscal O2 –O3 injection; Group C) patients submitted to two further sessions of intradiscal O2 –O3 injection. The results showed an improvement of pain scores in all groups, and a smaller disc area change in group B. Comparing the differences between pre- and post-treatment features among the three different groups of patients, we did not find any statistically significant difference. Correlation analysis did not show any statistically significant correlation between the morphological changes of the intervertebral disc and the clinical output scores. Conclusions: In our retrospective observation of partially responder patients, multiple intradiscal ozone injections were not associated with a higher disc shrinkage nor superior clinical outcome compared to a single intradiscal O2 –O3 application with an additional periradicular injection session.